Evolution of the Agricultural Sector in Pre-Revolutionary Russia: Regional Context - Natalia Rozinskaya (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The subject of the research in this article is the degree of development of the agricultural sector of the Russian Empire achieved in the pre-revolutionary period. An attempt is made to answer the question of the completeness of the agricultural revolution in the Russian Empire in the late 19th and early 20th centuries. Methods and materials. Methodologically, the author follows the institutional approach, sharing the view on the importance of the institutions’ analysis for proper explanation of socio-economic processes. The analysis carried out is based on the works of pre-revolutionary, Soviet, and post-Soviet authors, exploring the main factors of modernization at the regional level. The article uses extensive statistical material on the main indicators characterizing the evolution of agriculture. Analysis. The author proceeds from the fact that due to the very wide variety of socio-economic, geographical, and climatic conditions in the various territories that were part of Russia, significant scientific results can only be obtained by introducing a regional component into the analysis, that is, by considering the degree of completion of the agrarian revolution separately for the main regions. The article examines the characteristics necessary to answer the question of whether the agricultural sector of a given region complies with the criteria by which one can judge the completion of the agricultural revolution. The results obtained allow us to draw the next conclusions. First, in pre-revolutionary Russia there were very large regional differences, leading to limited usefulness of using values aggregated at the national level. Secondly, various criteria corresponding to a certain level of development did not coincide in individual regions of the Russian Empire. Thirdly, apart from two Baltic provinces, as well as Poland and Finland, which remained outside the scope of analysis, in the rest of the Russian Empire, the agricultural revolution in the pre-revolutionary period was far from complete.